An??lise de ades??o de compet??ncias organizacionais relacionadas ?? p??s-implementa????o de sistemas ERP em hospitais p??blicos da administra????o direta de S??o Paulo - Ribeiro, Nendy Temistocles (2015)
This research evaluates the adherence to organizational competencies that are linked to the universe of ERP systems management in the public hospital sector in its prospect of post-implementation. For this, use the theoretical framework associated with both the literature focused on the study of organizational skills as well as the literature on the ERP systems management, focusing on the public hospital sector. From the bibliographic review, study proposals were prepared that served as the basis for the development of a matrix of competencies with three public hospitals in the direct administration of the State of S??o Paulo. The methodology of the study predicted the development of multiple case study method by which the information gathered in organizations were analyzed together and in crosswise way, making possible the identification of the organizational competencies and their respective adhesions to the problem of research. Empirical evidence suggests that in fact there is a set of organizational competencies related to post-implementation of ERP applications, related to the quality of use and quality of information extracted; full IT management; technological innovation and safety requirements, confidentiality and reliability required by law specifically when it comes to health information. The results allowed defining strengths and weaknesses of which resulted in a contribution proposition to practice by means of a guide of best practices.